Using e-health to shorten treatment delay in patients with severe aortic stenosis. (13th November 2019) - Michel, M; Hammami, J; Vinet, M A; Picot-Ngo, C; Debroucker, F; Gilard, M; Chevreul, K
Abstract: Background: Transcatheter aortic valve replacement (TAVR) is a relatively new alternative to open surgery in patients with a severe aortic stenosis at high risk of surgery but there are important variations in treatment delay which can lead to increased morbidity and mortality. Those delays have many causes, including patients' unawareness of the urgency, delays in obtaining the necessary preoperative tests and organizational factors at the hospital level. The aim of our study was to co-construct an e-health tool for patients and their families to empower them and improve knowledge on the disease and TAVR to ultimately decrease the delay between the medical decision for TAVR and the actual procedure. Methods: A prospective study was first carried out to identify organizational factors associated with variations in treatment delay (both at the patient and hospital level). A preliminary survey was sent to all TAVR centers in France to understand and describe their organization. Descriptive analyses were then carried out on the answers. In a second step, two focus groups were carried with, the first with patients and carers and the second with healthcare professionals in order to elaborate the e-health tool. Results: A website has been developed for patients and their families. It includes information in video form on aortic stenosis and its different treatments, on TAVR, the necessary tests required prior to TAVR (with a geolocalisation of available facilities nearby so that patients may know where to go), and what they can expect during the hospital admission and after their release. Patients undergoing TAVR will be informed of the website's existence by their cardiologist. Web pages intended for healthcare professionals who are not TAVR specialists (general practitioners…) will also be available on the website. Conclusions: A cluster randomized controlled trial will now test the efficacy and efficiency of the e-health tool in reducing TAVR treatment delay. Key messages: We built a e-health tool in collaboration with patients, carers and healthcare professionals to increase patients' knowledge on aortic stenosis and TAVR. The website will provide information through videos to empower patients and ultimately decrease treatment delay and its associated morbi-mortality.